Advances in phosphonium-based ionic liquids and poly(ionic liquid)s as conductive materials. (November 2018) - Chen, Mingtao; White, B.T.; Kasprzak, Christopher R.; Long, Timothy E.
Graphical abstract: Abstract: Ionic liquids (ILs) and poly(ionic liquid)s (PILs) are attracting significant research interest as safe and efficient electrolytes. Most research efforts focus on nitrogen based ILs and PILs (ammonium, imidazolium, pyridinium, etc. ), while phosphorus based ILs and PILs have received relatively less attention despite exhibiting comparable ion conductivity over their nitrogen-based counterparts. In this review, we provide an overview of the structural elements in phosphorus based ILs and PILs that influence ion conductivity, such as ion size, ion polarizability, counterion selection, and backbone flexibility. We also highlight dominant physical parameters dictating ion conductivity including viscosity and glass transition temperature. A fundamental understanding of this structure-ion conductivity relationship will benefit the future rational design of phosphorus based ILs and PILs as electrolytes.